Profitability Stability and Liquidity Risk Mitigation: An Empirical Analysis of Indonesian Guarantee Institutions - Azizah Akbariani Ahmad; Husna Karimah; Muhammad Ariq Athallah Akbar (Warmadewa Management and Business Journal (WMBJ), 2026)
This study examines the resilience of profitability (Return on Assets) within Indonesian Guarantee Institutions, specifically focusing on withstanding the stress testing triggered by the COVID-19 pandemic. Adopting a quantitative approach, this research analyzed monthly secondary data from the Financial Services Authority (OJK) spanning January 2016 to June 2022 to capture the complete crisis cycle, from the initial stability phase to the subsequent recovery. The data analysis utilized Multiple Linear Regression via the Ordinary Least Squares (OLS) method on 76 observations following data transformation. The empirical results revealed a "Solvency Paradox," wherein the Solvency Margin Ratio (SMR) exerted a significant negative effect on ROA, suggesting capital allocation inefficiencies stemming from overly conservative management policies. In contrast, the Liquidity Ratio and Capital Adequacy Ratio demonstrated significant positive impacts, functioning as essential pillars of financial resilience and primary shock absorbers during periods of volatility. Furthermore, the Incurred Claims ratio and Gearing Ratio yielded no significant effect; this reflects the efficacy of risk transfer mechanisms through reinsurance in insulating net profits from operational shocks. Managerial implications emphasize the necessity of strategic repositioning—moving beyond passive capital accumulation toward the optimization of liquid investment instruments to sustain an equilibrium between financial security and profitability.